The Effect of Institutional Ownership, Capital Structure and Company Growth on Firm Value: Evidence from Indonesia - Ni Putu Mila Suhandi (International Journal of Digital Entrepreneurship and Business, 2021)
This study aims to examine the effect of institutional ownership, capital structure, and firm growth on firm value in companies listed on the Indonesia Stock Exchange (IDX). This study uses 32 companies in the LQ45 index listed on the Indonesia Stock Exchange, selected using the purposive sampling method from 2015 to 2019. This type of research is quantitative causality, which is analyzed using the multiple linear regression analysis methods with the help of SPSS version 24 to process data. The results showed that institutional ownership and firm growth positively affected firm value, while capital structure showed a negative effect on firm value. Research implications suggest that to improve the company’s management performance, providing the right decisions to obtain sustainable profits must also control efficiency and cost-effectiveness and manage the resources owned so that they can continue to grow and develop into a successful company.